1994
DOI: 10.1007/bf00000101
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between mycorrhizal fungi and other soil organisms

Abstract: Mycorrhizal fungi interact with a wide range of other soil organisms, in the root, in the rhizosphere and in the bulk soil. These interactions may be inhibitory or stimulatory; some are clearly competitive, others may be mutualistic. Effects can be seen at all stages of the mycorrhizal fungal life-cycle, from spore population dynamics (predation, dispersal and germination) through root colonization to external hyphal growth. Two areas that seem likely to be of particular importance to the functioning of the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(118 citation statements)
references
References 43 publications
3
107
0
5
Order By: Relevance
“…We presumed in that process AMF could lose the cation and release it in mycorhizosphere like carbon cases. Our observation was supported by Fitter and Garbaye (1993) that AMF can modify its interaction with other organisms in the soil, such as root-inhabiting nematodes and fungi, mutualists and notably nitrogen-fixing bacteria. In the mutualistic interaction, AMF showed its ability to work together with Azospirillum, Pseudomonas and Trichoderma.…”
Section: Resultssupporting
confidence: 74%
“…We presumed in that process AMF could lose the cation and release it in mycorhizosphere like carbon cases. Our observation was supported by Fitter and Garbaye (1993) that AMF can modify its interaction with other organisms in the soil, such as root-inhabiting nematodes and fungi, mutualists and notably nitrogen-fixing bacteria. In the mutualistic interaction, AMF showed its ability to work together with Azospirillum, Pseudomonas and Trichoderma.…”
Section: Resultssupporting
confidence: 74%
“…These compounds can range widely in function but a large proportion appear to be involved in inhibiting the growth of bacteria and other fungi (Keller et al, 2005). A major area of research in mycorrhizal ecology is the role of EM fungi in protecting plants from root pathogens (Marx, 1972;Fitter and Garbaye, 1994;Nagy and Fossdal, 2013). EM fungi have been shown in numerous studies to ward off fungal and bacterial root pathogens using secondary compounds.…”
Section: Other Secondary Compoundsmentioning
confidence: 99%
“…Not surprisingly, Rhizobium can also influence AM development and colonization. It was previously believed that AM colonization could be directly linked to inoculation with Rhizobium and the resulting increase in nitrogen fixation ͑El- Kherbawy et al 1989;Fitter and Garbaye 1994;Hodge 2000͒. However, Xie et al ͑1995͒ demonstrated that increased AM colonization in the presence of Rhizobium is actually linked to the production of plant flavonoids related to host nodulation factors triggered by inoculation with Rhizobium.…”
Section: Introductionmentioning
confidence: 99%